2018
DOI: 10.1177/1090198118757826
|View full text |Cite
|
Sign up to set email alerts
|

Social Environmental Correlates of Health Behaviors in a Faith-Based Policy and Environmental Change Intervention

Abstract: Diet and physical activity are behavioral risk factors for many chronic diseases, which are among the most common health conditions in the United States. Yet most Americans fall short of meeting established dietary and physical activity guidelines. Faith-based organizations as settings for health promotion interventions can affect members at multiple levels of the social ecological model. The present study investigated whether change in the church social environment was associated with healthier behavior at ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…However, despite well-designed and implemented interventions aimed at improving healthy eating and physical activity outcomes, the applied (clinical) effects are generally null to small (e.g. Bopp et al, 2012; Harmon et al, 2014; Hermstad et al, 2018; Hornbuckle et al, 2019; Lynch et al, 2019; Tristão Parra et al, 2018; Wilcox et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite well-designed and implemented interventions aimed at improving healthy eating and physical activity outcomes, the applied (clinical) effects are generally null to small (e.g. Bopp et al, 2012; Harmon et al, 2014; Hermstad et al, 2018; Hornbuckle et al, 2019; Lynch et al, 2019; Tristão Parra et al, 2018; Wilcox et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…13 However, much of the evidence about PA social norms is focused on family or friends and less attention has been placed on PA social norms in the church. A study with African Americans found that seeing fellow parishioners use PA facilities at the church was positively associated with parishioners' PA. 11 A qualitative study in San Diego, California, also found that church leaders and staff perceived that the PA behaviors of pastors were important for motivating Latinx parishioners' PA. 14 To our knowledge, no published quantitative study has examined the role of church PA social norms on Latinx PA.…”
mentioning
confidence: 99%
“…Such evidence is needed to identify appropriate targets for faith-based PA interventions, which could help optimize their effects on increasing PA among Latinx populations. 5 With respect to the social environment, several studies point to a positive association between PA social support from friends or family and Latinx individuals' PA. 7,10 Studies focused on churchgoing African Americans also show that social support from other church members may help reinforce PA among parishioners, 11,12 but such an association is not well understood among Latinx populations. PA social norms (behaviors or attitudes of others) are also associated with PA, independent of social support.…”
mentioning
confidence: 99%